A validated high‐performance liquid chromatography–tandem mass spectrometry method for quantification of gefitinib and its main metabolites in xenograft mouse tumor: Application to a pharmacokinetics study. (13th August 2019) - Zhao, Can; Zheng, Nan; Yang, Fen; Han, Shu‐Yan; Li, Ping‐Ping
Abstract: Monitoring gefitinib and its metabolites may help to explore the underlying mechanisms of gefitinib resistance. The concentration of gefitinib and its metabolites in tumor tissues could influence its anticancer activities more than that in the plasma. In the present study, a rapid and specific HPLC–MS/MS method was developed and validated to simultaneously determine gefitinib, M387783, M523595, M537194 and M608236 in tumor tissues of H1975 human lung cancer xenografts of nude mice. The established HPLC–MS/MS method was validated for specificity, linearity, accuracy and precision, matrix effect and recovery, carryover and dilution integrity, and analyte stability. The standard curves were linear ( r 2  ≥ 0.99) over the range of 0.5–100 ng/mL for M608236 and 1–200 ng/mL for gefitinib, M523595 and M537194 as well as M387783. The accuracy ranged from −8.35 to 6.03% relative error; and the precision was <15% relative standard deviation. Recoveries (87.74–99.96%) and matrix effects (86.60–106.40%) were satisfactory in the biological matrix examined. Stability studies showed that the analytes were stable during the assay procedure and storage. Finally, the validated method was successfully applied to study the pharmacokinetics profiles for gefitinib and its metabolites in nonsmall cell lung cancer (NSCLC) xenograft mouse tumors. Meanwhile, MTT assay showed that gefitinib had a more powerful inhibitory effect than its four major metabolites in H1975 NSCLC cells. This validated HPLC–MS/MS method may be applied to help understand the mechanisms of gefitinib resistance in EGFR‐mutant nonsmall cell lung cancer.